2023
DOI: 10.1038/s41598-023-29136-4
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial signature in lung cancer patients highlights specific taxa as predictors for durable clinical benefit

Abstract: We aimed to determine microbial signature linked with lung cancer (LC) diagnosis and to define taxa linked with durable clinical benefit (DCB) of advanced LC patients. Stool samples for microbial 16S amplicon sequencing and clinical data were collected from 75 LC patients (50 of which were treated with checkpoint inhibitors) and 31 matched healthy volunteers. We compared LC to healthy controls and patients with DCB to those without. LC patients had lower α-diversity and higher between-subject diversity. Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Our results agree with previous findings of studies of melanoma and other solid tumors treated with ICIs in which the responders presented enrichment of Clostridiales in the gut, compared to an increase in Hungatella in non-responders [31]. Derosa et al and Routy et al reported a correlation between ICI response and Akkermansia abundance [32,33], which was recently confirmed by an independent study [34]. Curiously, this genus was not represented in almost half of our patients and was a minority genus in the rest of the patients.…”
Section: Discussionsupporting
confidence: 93%
“…Our results agree with previous findings of studies of melanoma and other solid tumors treated with ICIs in which the responders presented enrichment of Clostridiales in the gut, compared to an increase in Hungatella in non-responders [31]. Derosa et al and Routy et al reported a correlation between ICI response and Akkermansia abundance [32,33], which was recently confirmed by an independent study [34]. Curiously, this genus was not represented in almost half of our patients and was a minority genus in the rest of the patients.…”
Section: Discussionsupporting
confidence: 93%
“…they collected stool samples from 75 lung cancer patients and 31 matched healthy volunteers for microbial 16S amplicon sequencing and clinical data, and found that patients with lung cancer had increased betweensubject diversity and α overall diversity. Speci cally, the abundance of the Clostridiales, Lachnospiraceae, and Faecalibacterium prausnitzii was reduced in lung cancer compared to controls [41] , those bacterial taxon are all belong to the order Eubacteriales. In our study, genus LachnospiraceaeUCG008 had a adverse effect on SCLC, while genus LachnospiraceaeNK4A136group showed an protective impact on SCLC, which are the subclass of Lachnospiraceae.…”
Section: Discussionmentioning
confidence: 96%
“…Alistipes putredinis was also found to be enriched in the treatment response group in NSCLC receiving immunotherapy [ 25 ]. High Alistipes onderdonkii expression is associated with lasting clinical benefits in advanced NSCLC [ 39 ]. Alistipes may help protect against certain conditions such as liver fibrosis, colitis, cancer immunotherapy, and cardiovascular diseases [ 40 43 ].…”
Section: Discussionmentioning
confidence: 99%